BUNGKAMNYA ANAK ATAS PENGALAMAN KEKERASAN BULLYING. SYNDROME PENYESUAIAN DIRI ROLAND SUMMIT - A.N, M.N Ahla (KOMUNITAS, 2017)
Socialization is education received by society. The first socialization is the family that is the beginning of learning after human beings are born. After the family, the environment is the socialization of children after the family, starting from peers and neighbors. The third socialization is the school (formal education), in this school, there are many children begin to develop their characters. The children can become naughty because of their negative society. In this research, the researcher examined the children’s silence of bully victims at MA Masyitoh Yogyakarta. The method used was qualitative with purposive sampling technique with students at MA Masyitoh. The results of this research indicated that the children do not dare to reveal that they are the victims of bully becauseof : 1. Secret, 2. Powerlessness, 3. Self-Adjustment, 4. Delay, and 5. Recall.